Increased incidence of inflammatory bowel disease on etanercept in juvenile idiopathic arthritis regardless of concomitant methotrexate use - Van Straalen, Joeri W (2022)
Objective: To describe risk factors for IBD development in a cohort of children with JIA. Methods: JIA patients who developed IBD were identified from the international Pharmachild register. Characteristics were compared between IBD and non-IBD patients and predictors of IBD were determined using multivariable logistic regression analysis. Incidence rates of IBD events on different DMARDs were calculated, and differences between therapies were expressed as relative risks (RR). Results: Out of 8942 patients, 48 (0.54%) developed IBD. These were more often male (47.9% vs 32.0%) and HLA-B27 positive (38.2% vs 21.0%) and older at JIA onset (median 8.94 vs 5.33 years) than patients without IBD development. They also had more often a family history of autoimmune disease (42.6% vs 24.4%) and enthesitis-related arthritis (39.6% vs 10.8%). The strongest predictors of IBD on multivariable analysis were enthesitis-related arthritis [odds ratio (OR): 3.68, 95% CI: 1.41, 9.40] and a family history of autoimmune disease (OR: 2.27, 95% CI: 1.12, 4.54). Compared with methotrexate monotherapy, the incidence of IBD on etanercept monotherapy (RR: 7.69, 95% CI: 1.99, 29.74), etanercept with methotrexate (RR: 5.70, 95% CI: 1.42, 22.77) and infliximab (RR: 7.61, 95% CI: 1.27, 45.57) therapy was significantly higher. Incidence on adalimumab was not significantly different (RR: 1.45, 95% CI: 0.15, 13.89). Conclusion: IBD in JIA was associated with enthesitis-related arthritis and a family history of autoimmune disease. An increased IBD incidence was observed for etanercept therapy regardless of concomitant methotrexate use.